ANALYSIS SECTIO CAESAREA AT PIRNGADI HOSPITAL IN 2019 - Erika, Rahma Fidrayana Fitri (STIKes Mitra Husada Medan, 2020)
Background: Around the world, there is an increase in the number of sectio caesarea in developed and developing countries. The decision to have a sectio cesarean is what the best for saving mother and child. Indications for a sectio cesarean can be divided into absolute and relative indications. The most important indications for a sectio cesarean include breech presentation, prolonged birth including failure to progress in labor, intrauterine hypoxia and anything to do with previous a sectio cesarean.Method: The research was observational study with case control design. The aims were to explain the medical factors influencing the caesarean Section in that hospital. The population were the mothers with childbirth in hospital. The sample used were 46 patient that undergo sectio cesarea and partus spontaneous.Result: Based on the results of research conducted at Pirngadi Hospital Medan in 2019, it can be seen that the most frequent labor cases were found sectio cesarea are 46 patients. The most common cause was found such as fetal abnormalities (malposition) 31 cases (67%), while uterus contraction (his) abnormalities were 6 cases (13%) least found cases.Conslusion: The most indications for cesarean section are fetal abnormalities compared to his abnormalities and passageway abnormalities. Antenatal care (ANC) routinely performed on pregnant women to observe pregnancy development and fetal growth in order to reduce morbidity and mortality rates for mothers and childbirth.Keywords: Sectio Caesarea, medical factors